2010
DOI: 10.1002/smi.1312
|View full text |Cite
|
Sign up to set email alerts
|

Academic burnout profiles in Korean adolescents

Abstract: The purpose of this study is to identify specifi c burnout patterns among Korean students. Using a cluster analysis procedure and the Maslach Burnout Inventory-Student Survey, four clusters were identifi ed: (1) distressed group;(2) laissez-faire group; (3) persevering group; and (4) well-functioning group. In addition, the results of categorical regression analysis indicated that self-esteem and Grade Point Average (GPA) were good discriminators between the four clusters. Specifi cally, students who self-iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 46 publications
(54 reference statements)
4
54
1
2
Order By: Relevance
“…Students' burnout can be noticeable in several ways like; feeling exhausted because of academic demands, having a cynical and detached attitude towards their studies, and feeling incompetent as a student (Lee et al, 2010). Thus, a student version of Maslach Burnout Inventory, i.e.…”
Section: Students' Academic Burnoutmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' burnout can be noticeable in several ways like; feeling exhausted because of academic demands, having a cynical and detached attitude towards their studies, and feeling incompetent as a student (Lee et al, 2010). Thus, a student version of Maslach Burnout Inventory, i.e.…”
Section: Students' Academic Burnoutmentioning
confidence: 99%
“…It has been used by various researchers like Esteve (2003) Lee et al (2010), Breso et al (2011). Meanwhile, among all of these researchers, only Jia et al (2009) studied burnout levels of architecture students and observed "low" burnout levels for both emotional exhaustion and academic efficacy and "very low" burnout levels for cynicism.…”
Section: Students' Academic Burnoutmentioning
confidence: 99%
“…Schaufeli et al have developed a student version of the Maslach Burnout Inventory (MBI-SS) (Schaufeli et al 2002). Many studies have used this scale to examine student's burnout levels (Esteve, 2003;Breso et al, 2010;Gan and Shang, 2007;Hu and Schaufeli, 2009;Jia et al, 2009;Lee et al 2010;Lingard, 2007;Morgan, B., 2008;Zhang et al 2007;Salanova et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License workloads, assignments with deadlines, and other responsibilities that cause them to develop burnout syndromes (Erturgut and Soyşekerci, 2010;Law, 2010;Lee et al, 2010;Mostert et al, 2007;Parker and Salmela-Aro, 2011). "Burnout among students refers to feeling exhausted because of study demands, having a cynical and detached attitude toward one's study, and feeling incompetent as a student" (Schaufeli et al, 2002, p. 465).…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of burnout that occurs during college years manifest in both pre-service and in service years. For example, studies with students revealed that burnout has a significant negative impact on academic performance (Balkıs et al, 2011;Lee et al, 2010;Yang, 2004) and commitment (Jia et al, 2009), and that there is a negative correlation between burnout and engagement (Alarcon et al, 2011;Kutsal and Bilge, 2012;Mostert et al, 2007;Salanova et al, 2010;Uludağ and Yaratan, 2010;Zhang et al, 2007), between burnout and self-esteem (Lee et al, 2010), between burnout and life satisfaction (Chang et al, 2011;Capri et al, 2012), and between burnout and student departure (Kelly et al, 2012). Burnout may result indissatisfaction from school, low commitment, skipping classes, intention to leave college, and low academic performance (Law, 2007;Maslach and Leiter, 2008).…”
Section: Introductionmentioning
confidence: 99%